Chapter 35: Potato Production in Florida - Chad M. Hutchinson; Eric H. Simonne; George J. Hochmuth; Donald N. Maynard; William M. Stall; Stephen M. Olson; Susan E. Webb; Timothy G. Taylor; Scott A. Smith (EDIS)
This document is HS733, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.